Methyl pyridine derivatives of 14-membered tetraaza macrocycles. A new host with high selectivity for cadmium - Costa, J (2015)
Two N-(2-pyridylmethyl) derivatives of a 14-membered tetraaza macrocycle containing pyridine have been synthesized, L-1 and L-2. The protonation constants of these compounds and the stability constants of complexes of both ligands with Co2+ to Zn2+, Cd2+, Pb2+, Fe3+ and In3+ were determined by potentiometric methods at 25 degrees C and ionic strength 0.10 mol dm(-3) in KNO3. The values of the protonation constants for L-1 and L-2 are quite different. The metal complexes of both ligands present lower values of stability constants than expected. The only exception is the case of the Cd2+ complex with L-2 which exhibits a particularly high stability constant, indicating that this ligand has a remarkable selectivity for this metal ion relative to zinc. The Cd2+ complex seems to be the only one to bond to all the donor atoms of the ligand or at least to more than the other metal ions studied. The pM values determined at physiological pH, which take into account the competition of the protons for the ligand, have shown that L-2 is the most selective compound for cadmium relative to zinc. The single crystal structure of [CuL2][ClO4](2) determined by X-ray diffraction has shown that the co-ordination geometry around the copper atom can be described approximately as a distorted square pyramid. To achieve this geometric arrangement the macrocycle adopts a folded conformation. Furthermore the nitrogen atom of one free pyridylmethyl pendant arm is directed towards the copper centre leading to a distance between these two atoms of 3.304(11) Angstrom, which suggests a weak bonding interaction consistent with a [5+1] co-ordination.